Influence of acculturative stress on marital satisfaction: Moderation effect of gender role and communication styles in Pakistani immigrants. Issue 5 (20th October 2019) - Jibeen, Tahira
ABSTRACT: Using a sample of 115 first-generation married immigrant Pakistani residing in Toronto, Canada, this study assessed the moderating effect of couples' communication patterns (warm and moderate hostility) and gender role beliefs (transcendence and gender-linked beliefs) on the link between acculturative stress and satisfaction with marriage. Participants completed a demographic information sheet, the Multidimensional Acculturative Stress Scale (MASS), the Social Roles Questionnaire (SRQ), the Behavioral Affect Rating Scale (BARS) and the Relationship Assessment Scale (RAS). Regression analyses indicated that gender-linked beliefs and hostile styles of communication played a moderating role between acculturative stress and marital satisfaction, decreasing marital satisfaction, while gender-transcendent beliefs and a warm style of communication supported the relationship and enhanced the marital satisfaction. Clinicians and researchers need to address the communication styles and beliefs of Pakistani immigrants within their marital relationship to get a fuller picture of it.